Surveillance of Berberis Species across Poonch Division of Azad Jammu and Kashmir: Diversity of Berberis Species - Rizwan Azim,; Shahid Iqbal Awan,; Muhammad Ilyas,; Arifa Khan, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Berberis is one of the most important medicinal plant and it has a great medicinal value. Berberis has such pronounced medicinal values that it is used to cure many diseases and has exhibited great therapeutic effects among the local communities throughout the world. Diversity of Berberis is uncertain to great extent in Poonch division of Azad Jammu and Kashmir. Berberis specimens were collected from four districts comprising fifteen tehsils of Poonch division of Azad Kashmir. About 40 prominent locations were visited during flowering and fruiting stages during 2016-17. A total of seven species and a sub species were identified on the basis of morphological studies. Studies showed that identified Berberis species were present in all the four districts. Shanon and Simpson indices were used for calculating diversity of Berberis species in the study area along with calculating species evenness and equitability. Diversity indices indicated that there was moderate diversity of Berberis species within different districts and different tehsils. Simpson diversity index indicated that there is an 87 % chance that two individuals selected randomly from the study area would be different. Species evenness indicated that each specie identified from each tehsil had maximum chance of occurrence and each identified species is present in every tehsil. Species equability also indicated similar kinds of results which indicated that different species were evenly distributed in each tehsil. It was concluded that there is moderate diversity of Berberis species in Poonch division of Azad Jammu and kashmir. All the identified species were present in all the districts. The present study will advance our knowledge regarding identification and distribution of Berberis species in Poonch division.